The Woodcraft Girls in the City - Roy, Lillian Elizabeth, 1868-1932 (Salt Lake City, UT : Project Gutenberg, 2011)
"The Woodcraft Girls in the City" by Lillian Elizabeth Roy is a novel written in the early 20th century. The story follows a group of young girls known as the Woodcrafters as they navigate life in the city after spending a summer at camp. The central characters include Zan Baker, Hilda Alvord, Jane Hubert, and their Guide, Miss Miller, who collectively explore the joys and challenges of maintaining their Woodcraft spirit in an urban setting. At the start of the narrative, the Woodcraft Girls are reuniting after their summer camp experience, excitedly discussing plans for a Winter Camp and the possibility of welcoming new members into their band. Zan announces an invitation from their Guide, Miss Miller, for a tea gathering to discuss these plans. During the meeting, the girls express their thoughts on city life compared to their delightful days at camp, and they brainstorm creative ideas for outdoor sleeping arrangements. The opening sets the stage for the camaraderie, challenges, and character development that will unfold as they integrate new members into their circle while managing the dynamics of city living. (This is an automatically generated summary.)
Release date is 2011-03-17
Produced by Roger Frank and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Camping -- Juvenile fiction; Girls -- Societies and clubs -- Juvenile fiction; City and town life -- Juvenile fiction; Handicraft -- Juvenile fiction